Exclusão social e projetos habitacionais. Um estudo sobre conjuntos habitacionais, segregação e exclusão social em Natal/RN - Medeiros, Amanda Kellen Silva de (2012)
In Natal s urban growth process it is given that the performance period of the National Housing Bank (BNH, 1964-1986) was marked by the intense expansion of the urban grid and configuration of outskirts, through the construction of social housing developments. Implanted in segregated areas of the existing formal city, the population installed in these complexes was also excluded from their rights, considering that the housing defines itself not only by the physical dwelling, but also by its access to urban infrastructure, facilities, services, and others. From this reality and the verification of the city s exclusion and sociospatial segregation processes, we aimed to quantitatively demonstrate levels of social exclusion in Natal, based on the methodology developed by Sposati (2000) and adapted by Genovez (2002), which relates IBGE s (Brazilian Institute of Geography and Statistics) database underlying variables such as income, schooling and dwelling s quality. The research unveiled some spatial patterns promoted by the social housings: in these areas islands were developed with higher indicators than surrounding areas, revealing internal hierarchies in the city s outskirts